TRADISI PENGAJIAN KITAB TURÂTS MELAYU- ARAB DI PULAU SERIBU MASJID DAN SERIBU PESANTREN, LOMBOK, INDONESIA - Fahrurrozi Fahrurrozi (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This paper focuses on the recitation and preservation of Arab- Malay Turast book reviews in Lombok, West Nusa Tenggara, which clas- sified into four sections: 1) Recitals ( Khalaqah ) 2) Public preaching from The Majelis Dakwah (Islamic Da’wa council) and The Para Tuan Guru’s ( Asâtiz) focused group studies ( Majelis Taklim ). 3) Formal material stud- ies at Islamic boarding schools ( pesantren ) 4) Reading of Malay Islamic books by commoner in several religious activities. This study is signifi- cant because, The Arabic-Malay books are considered as a treasure for the Archipelago and yet, it is starting to fade among the Malay Islamic society. This also seen from the more and more lack of interest in speak- ing and writing using Arab-Malay language. Unlike the era of 18-19 cen- tury, where Arabic-Malay is considered as the most important language among the Malay communities, since it was used in communication and media literacy. The most prominent stretch of the Malay Literacy could be seen in the 14th to 16th century where many books are translated, composed or adapted into several languages, includes Malay, Javanese, Sundanese, Bugis and many others. In fact, some Islamic Indonesian au- thors also re-wrote the books with similar style and content closed to the original book. Moreover, the tradition of reading and reviewing Islamic Malay books have long taken place in the midst of society. It was both read on the public preaching or individually, such as the research of the Sabilal Muhtadin fiqh’s book by Syeikh Arsyad Banjar; Kitab Perukunan Ibadah Doa dan Zikr (worship, praying and remembrance), Hidayatus Salikin on Sufism; Fiqh’s and Sufism’s Al-Muhtadi Masa’ilah which is also commonly used in nyaer form (reading the Arab-Malay books in a singsong manner); Qishashul Anbiya ; Kifayah al-Muhtaj; Nur Muhammad , and the story of the Husain bin Ali’s killing.